POLEMIK PEMERINTAHAN DESA DINAS BONGKASA PERTIWI DALAM PENGEMBANGAN STRATEGI DESA WISATA DIMASA PANDEMI COVID-19 - Wulandari, Ni Komang Tri; Wirantari, I Dewa Ayu Putri; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2022)
Bongkasa Pertiwi Village is one of the tourist villages established by the Badung Regency government based on Badung Regent Regulation Number 47 of 2010. With the outbreak of the Covid19 Pandemic, many polemics have arisen in carrying out the strategies that have been designed due to the decline in tourist visits. Analysis using SWOT analysis and SWOT matrix. The results of this study indicate that there are still several obstacles such as the tourism village development strategy through the DED concept that cannot be realized due to the Covid-19, the role of traditional villages and service villages in the development of sustainable tourism villages has not been maximized, tourism has not been able to contribute to PADes. Implementation of program strategies that have not been optimal due to the outbreak of the covid-19 pandemic, low human resources, minimal policies in regulating the management of tourist villages. Keyword : tourist village, strategic management, SWOT analysis